Mechanisms of Spontaneous Climbing Fiber Discharge-Evoked Pauses and Output Modulation of Cerebellar Purkinje Cell in Mice - Jin, Xian-Hua; Wang, Hong-Wei; Zhang, Xin-Yuan; Chu, Chun-Ping; Jin, Yuan-Zhe; Cui, Song-Biao; Qiu, De-Lai (Frontiers in Cellular Neuroscience, 2017)
Climbing fiber (CF) afferents modulate the frequency and patterns of cerebellar Purkinje cell (PC) simple spike (SS) activity, but its mechanism is unclear. In the present study, we investigated the mechanisms of spontaneous climbing fiber discharge-evoked pauses and the output modulation of cerebellar PCs in urethane-anesthetized mice using in vivo whole-cell recording techniques and pharmacological methods. Under voltage-clamp recording conditions, spontaneous CF discharge evoked strong inward currents followed by small conductance calcium-activated potassium (SK) channels that mediated outward currents. The application of a GABAA receptor antagonist did not significantly alter the spontaneous SS firing rate, although an AMPA receptor blocker abolished CS activity and induced significantly increased SS firing rates and a decreased coefficient of variation (CV) SS value. Either removal of extracellular calcium or chelated intracellular calcium induced a decrease in amplitude of CS-evoked after-hyperpolarization potential (AHP) accompanied by an increase in SS firing rate. In addition, blocking SK channels activity with a selective antagonist, dequalinium decreased the amplitude of AHP and increased SS firing rate. Moreover, we found repeated CF stimulation at 1 Hz induced a significant decrease in the spontaneous firing rate of SS, and accompanied with an increase in CV of SS in cerebellar slices, which was also abolished by dequalinium. These results indicated that the spontaneous CF discharge contributed to decreasing SS firing rate via activation of SK channels in the cerebellar PCs in vivo in mice.